Identification and pathogenicity of Alternaria species causing leaf blotch and fruit spot of apple in California - Karina ELFAR; Marcelo I. BUSTAMANTE; Molly ARREGUIN; Mohamed T. NOURI; Akif ESKALEN (Phytopathologia Mediterranea)
In late summer 2020, symptoms of leaf blotch and fruit spot were observed in two different commercial apple orchards (cultivars ‘Pink Lady’ and ‘Modi’) in San Joaquin County, California, USA. Ninety Alternaria isolates were obtained from symptomatic leaves and fruits collected from the orchards. Based on morphological characteristics of the colonies, sporulation patterns, and conidia, the isolates were preliminarily separated into three morphogroups, tentatively identified as A. alternata, A. tenuissima and A. arborescens. Multi-locus phylogenetic analyses, using nucleotide sequences of plasma membrane ATPase, calmodulin, and Alternaria major allergen genes, showed that the isolates initially identified as A. tenuissima clustered with strains of A. alternata, following the current taxonomical arrangement of the genus. Pathogenicity tests on detached wounded apple leaves and fruits, using representative isolates of the three morphogroups, fulfilled Koch’s postulates. This is the first report of A. alternata and A. arborescens as causal agents of leaf blotch and fruit spot of apple in California.